Economic Policy Coordination in the EMU. How Much Scope will There be Within the Framework of the Stability and Growth Pact? - Fritz Breuss; Andrea Weber (Austrian Institute of Economic Research (WIFO), 1999)
With a large-scale econometric world model we derive policy multipliers and the parameters for the utility functions for 10 EMU countries and for the ECB. The gains from cooperation are calculated by comparing two equilibria, a Nash and a cooperative equilibrium. The cooperative equilibrium is the result of the maximization of a weighted utility function for Euroland as a whole with the targets output gap and inflation. In the case of a "full" cooperation, where the 10 EMU countries coordinate their fiscal policy with the monetary policy of the ECB the welfare gains are very large for the whole Euro zone. However the strong fiscal and monetary policy impulses as a result of this optimization procedure lead, firstly, to a violation of the fiscal targets (budget deficit, public debt) of the Stability and Growth Pact which limits the room for manoeuvre of fiscal policy of the EMU member states in stage III of EMU. Secondly, we find that not in all countries cooperation leads to welfare gains, a result which is not Pareto efficient. Therefore, by considering these two constraints (Pareto optimality and SGP objectives) the constrained optimization results in a solution in case of "full" cooperation which drives most countries back to the Nash position of the baseline. In addition, a "partial" cooperation in which the ECB stays aside and only the fiscal policies of the EMU member countries are taking part, leads to a very small welfare improvement and violates again (only to minor degree the Pareto optimality condition). The optimal fiscal policy impulses are very modest.
Keywords: C70; E52; E58; E62; 330; EMU; policy coordination; fiscal and monetary policy; Stability and Growth Pact; Eurozone; Internationale Wirtschaftspolitik; Geldpolitik; Finanzpolitik; EU-Staaten